Perception of brand management - Singh, Ram Babu , 1955- (ALP Books, 2011)
This triumvirate of branding, packaging, and labeling has been accorded considerable attention in recent years because of fundamental changes in the American economy. The shift in population from rural to urban areas, the higher standard of living which permits a greater variety of purchases and allows purchase of products in containers, even though the price is thereby increased, better transportation and communication all have had their effect on preparation of the product for the market